If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2x + 3) = 8x + 15 Reorder the terms: 6(3 + 2x) = 8x + 15 (3 * 6 + 2x * 6) = 8x + 15 (18 + 12x) = 8x + 15 Reorder the terms: 18 + 12x = 15 + 8x Solving 18 + 12x = 15 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 18 + 12x + -8x = 15 + 8x + -8x Combine like terms: 12x + -8x = 4x 18 + 4x = 15 + 8x + -8x Combine like terms: 8x + -8x = 0 18 + 4x = 15 + 0 18 + 4x = 15 Add '-18' to each side of the equation. 18 + -18 + 4x = 15 + -18 Combine like terms: 18 + -18 = 0 0 + 4x = 15 + -18 4x = 15 + -18 Combine like terms: 15 + -18 = -3 4x = -3 Divide each side by '4'. x = -0.75 Simplifying x = -0.75
| 1/2(91/2)(5) | | 12x-18=6x-6 | | -5t^2+45t=0 | | 16x^3-3x^4=c | | a-6=7a+14 | | 12x-18=12x-12 | | 18x+3x=-2x+3 | | x^2-3x+16=4-10x | | 3x-2=-7x+9+2x | | 3+7*x=17 | | (x^2)+x=182 | | A/6=1/2 | | (5sin^2x+4cosx-4)ln(x-7)=0 | | (x^2)-55*x=-750 | | (x^2)-45*x=-324 | | 0.4x^2+x-5.6=0 | | 2vt-gt^2=0 | | 3x=14+9x | | x^2+4.5*x+1=0 | | D=3a(bc) | | 42P=0.85N | | 12/44=x/.05 | | 0.85=42 | | 4secx+7=0 | | P=42N | | 4sec+7=0 | | (x*x)-(8*x)=1280 | | 9x-2=-10+x | | h(t)=23t-5t^2+2 | | (x+3)*(x+29)=360 | | 5x^2+Y^2=14 | | 4*(x+15)=24 |